UNISON framework of data-driven innovation for extracting user experience of product design of wearable devices. (September 2016) - Lin, Kuo-Yi; Chien, Chen-Fu; Kerh, Rhoann
Highlights: A data mining and data-driven framework is constructed to extract user preferences effectively. An empirical study was conducted to derive useful rules for product form of wearable devices. Specific rules are employed to support product design based on user experience. The proposed approach was validated and implemented in real settings. Abstract: For consumer products, the time-to-market pressure and market share competition are intensive due to the shortening product life cycles. Product form design that contributes to the user experience (UX) is critical to distinguish the product from others. However, few studies have been done for exploring the relationship between UX and the design of product form. To fill the gaps, this study aims to propose a UNISON framework for data-driven innovation to capture the user experience and preference among the factors of product form designs to derive useful rules. An empirical study was conducted for the product design of wearable devices of a world leading Electronics Manufacturing Service (EMS) company with experimental designs of the subjects with different backgrounds to extract their UX to derive design rules. The results have shown practical viability of the proposed approach to assist the designers to develop product design strategies based on the consumer characteristics and the product UX to launch the preferred products to the corresponding customers to enhance customer satisfaction.